Identifying strategies to reduce the shortage of Dutch registered nurses; analysis of prognostic data from a national database - Renate F. Wit; Art van Schaaijk; Ronald S. Batenburg (BMC Health Services Research, 2026)
Abstract Background Rising healthcare demand is putting significant strain on the nursing workforce, leading to increased stress, absenteeism, and exits from the profession among registered nurses (RNs). In response, various initiatives are being implemented to ensure sustainable healthcare provision amid this growing demand. The aim of this study is to project future supply and demand for registered nurses in the Netherlands. Additionally, the study seeks to identify the key factors contributing to the nursing shortage and explore potential strategies to mitigate this problem. Methods This study used data from the Dutch Continuous Monitor of the Healthcare and Welfare Labour Market (AZW), which is based on a combination of surveys and administrative sources. The AZW forecasting model was used to perform what-if analyses, analysing the gap between the supply and demand of registered nurses after changing the values of various factors. The analysis involved adjusting factors such as average weekly working hours, the absenteeism rate, and nurse entry and exit rates to generate projections for the future nursing workforce. Results Projections indicate that the nursing shortage in the Netherlands will grow from a relative shortage of registered nurses of 5.7% of the nurse workforce demand in 2023 to 14.6% by 2033. The what-if analyses show that no single strategy will completely eliminate this shortage. The most effective approach of the scenarios we assessed is reducing nurse exit rates by 20% combined with increasing working hours by 1.5 hours per week, which potentially reduces the projected shortage to 1.4% by 2033. Retaining the nursing workforce is identified as the most impactful strategy for addressing the supply-demand gap. Conclusion Tackling nursing shortages in the Netherlands will require prioritizing nurse retention and encouraging increases in working hours in addition to recruitment efforts. Furthermore, reducing the demand for healthcare services will be important in achieving a balance between the supply of and demand for nurses, but is also a more complex challenge.